STRATEGI KOMUNIKASI LINTAS BUDAYA DALAM MENINGKATKAN KEBERHASILAN NEGOSIASI BISNIS - M. Zulfiyan Yahya; Maya Nur Aini; Asna Sendya Eka N.; Tiya Ameiliya; Anang Haris Firmansyah M.Pd (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine effective cross-cultural communication strategies in improving business negotiation success in the era of globalization. Cross-cultural communication is one of the key determinants of business negotiation success because each individual carries different values, norms, and customs. This study uses a literature review method by analyzing various research sources related to cross-cultural communication and business negotiation. The results show that the success of cross-cultural business negotiations is heavily influenced by the ability to understand cultural differences, verbal and nonverbal communication skills, trust-building capabilities, flexibility in negotiation approaches, and understanding of cross-cultural business ethics. The main barriers in cross-cultural communication include ethnocentrism, stereotypes, language differences, and culture shock. Strategies that can be applied include cross-cultural training, utilization of communication technology, development of cultural tolerance, and open dialogue between groups. These findings provide practical contributions for business actors interacting in multicultural environments to achieve mutually beneficial agreements.